Covid-19 and sustainable development in Europe: a temporal comparison - Bartiromo, Marianna (Revista de Estudios Andaluces, 2022)
Covid-19 has posed major challenges globally. One of these is undoubtedly the achievement of the Sustainable Development Goals (SDGs) of the 2030 Agenda.This study aims to analyze, in a time perspective, the effects of the pandemic on the levels of sustainable development achieved in Europe. To measure the impact of Covid-19, 3 different sustainability indices (SIs) will be constructed referring to 2015, 2018 and 2020. To construct these indices, 17 indicators (one per SDG) from Eurostat’s free database will be used. The Adjusted Mazziotta-Pareto Index (AMPI) method will be used to aggregate these indicators. This method relying on a Min-Max transformation allows for an absolute time comparison. In addition, this method allows for high replicability of results. Furthermore, in order to capture the differences between different European specificities, a hierarchical clustering will be performed according to the Ward method. The results confirm the negative effects of Covid-19. In fact, there is a general worsening of sustainable development levels between 2015 and 2020.